Prevalence and Determinants of Early Antenatal Care Visits Among Pregnant Women Attending Antenatal Care in Rural Gambia - Babucarr Jassey (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
An estimated 303,000 maternal deaths occurred worldwide in 2018. The Gambia has a MMR of 400/100,000 live births. In the Gambia, 24% of pregnant women receive antenatal treatment four times. Insufficient knowledge of the value of prenatal care and lack of subsidized ANC services are the main causes of the growing maternal and newborn mortality rate in Gambia. The study's major goal was to investigate factors influencing pregnant women in rural Gambia who attend early prenatal care. A cross-sectional community-based survey using structured questionnaires was used for the investigation. Cluster random sampling was utilized in the study to choose samples from 5 distinct districts. The study found that socioeconomic factors, economic factors, and accessibility to antenatal care service center influenced early ANC Attendance. After multivariate analysis, marital status, number of children, mother's occupation, cultural acceptance, and education level significantly correlate with early ANC attendance. The Foni district's early ANC attendance rate (ANC) was comparatively low compared to WHO criteria and fell short of the national requirement. This finding may explain the high mother and child mortalities observed in the Foni districts. The study found significant knowledge of ANC services, but this did not help increase early ANC attendance rate.